A processing technology of grooves by picosecond ultrashort pulse laser in Ni alloy: Enhancing efficiency and quality. (April 2019) - Zhao, Wanqin; Wang, Lingzhi; Yu, Zhishui; Chen, Jieshi; Yang, Jin
Highlights: Multi-scan processing could increase the depths of grooves. Multi-scan processing optimizes sidewall and bottom morphology of grooves. Multi-scan processing could enhance the efficiency and quality of grooves. Temporary saturation and the bending for deep groove processing are presented. The related reasons and the solutions on the deep groove bending are discussed. Abstract: The comparative study is presented of grooves ablation for the single- and multi-scan processing technology in Ni alloy using a 10 ps pulse laser with the wavelength of 532 nm and the repetition rate of 1 kHz. Results show, when the N (the effective ablation pulse number per unit area), for the single-scan processing of grooves, have been divided into multiple groups and combined with multiple times ablation, namely the multi-scan processing, the groove depth and morphology quality could be enhanced effectively. In addition, the temporary saturation of the groove depth and the bending on the deep groove bottom are reported. Especially for the bending phenomenon which hinders the further deepening of the groove, the related reasons and the solutions are discussed.